Question analysis in indonesians’ new curriculum secondary mathematics textbook - Raditya, Aji; Saputra, Nisvu Nanda (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study analyzed questions (examples and exercises) in the Numbers chapter on Indonesians’ new curriculum (Kurikulum Merdeka) mathematics textbooks for grade 7. An analytical framework developed for mathematics textbooks question analysis had seven dimensions: Mathematical Activity, Problem Complexity, Answer Type, Contextual Situation, Response Type, Mathematical Questions, and Data Problem. The result showed that the Indonesians’ new curriculum of secondary mathematics textbooks contains more balanced question types. In Mathematical Activity question types, only 46.73% of questions were about counting and using count operations. The questions about interpretation were 28.97% and questions that needed an argument or logical reasoning were 15.58%. In question type analysis, 22.12% were open-ended questions and 77.88% were close-ended questions. We also found that there were no multiple choice question types in Indonesians’ new curriculum (Kurikulum Merdeka) mathematics textbooks for grade 7. On the other hand, we also found questions with insufficient data (12.15%) and extraneous data (7.48%).